Case report: Fatal neonatal sepsis associated with Escherichia fergusonii infection in a common bottlenose dolphin (Tursiops truncatus) - Su-Min Baek; Su-Min Baek; Seoung-Woo Lee; Seoung-Woo Lee; Tae-Un Kim; Ji Hyung Kim; Ji Hyung Kim; Young-Jin Lee; Jae-Hyuk Yim; Woo Jun Kim; Seong-Kyoon Choi; Jee Eun Han; et al. (Frontiers in Veterinary Science, 2023)
A 25-day-old male common bottlenose dolphin (Tursiops truncatus) died suddenly while swimming at a dolphinarium. The gross examination revealed ulceration on the dorsal and pectoral fins and rostrum. Severe congestion, hemorrhage, and edema were observed in the gastrointestinal tract, liver, mesenteric lymph nodes, lungs, and kidneys. Fibrinosuppurative arthritis of the atlantooccipital joint and extension of fibrin into the spinal canal caused compression of the spinal cord. Histopathological examination revealed tracheitis, fibrinosuppurative bronchopneumonia and enteritis. In the central nervous system, meningeal vessel congestion in the brain, and intraparenchymal hemorrhages with neurodegeneration were observed in the spinal cord. Based on the histopathological findings, representative samples, including lung, liver, mesenteric lymph node, blood obtained from the jugular vein, and fluid sample of the ascites, were inoculated on tryptic soy agar and blood agar for routine bacterial isolation. Each isolated bacterial colony was streaked aseptically onto tryptic soy agar and blood agar for pure culture. After then, polymerase chain reaction (PCR) was performed for further identification of pathogenic microorganisms. PCR identified Escherichia fergusonii, Shewanella haliotis, Enterococcus faecalis, and Staphylococcus schleiferi. E. fergusonii was considered the primary etiologic agent in this case since it was the only species identified in all representative samples. The cause of death in this animal was E. fergusonii sepsis. To the best of our knowledge, this is the first case of neonatal sepsis associated with E. fergusonii infection in a dolphin, and suggests E. fergusonii as an opportunistic pathogen associated with sepsis in dolphins.